Jubilee - Walker, Margaret 1915-1998 (Mifflin, 1966)
The fortunes of a mulatto girl--as a slave during the Civil War and then as a woman freed by the Emancipation Proclamation.
Keywords: Geschichte; Schwarze. USA; Sezessionskrieg (1861-1865); Sklaverei; Weibliche Schwarze. Amerika; African American women -- Fiction; Racially mixed people -- Fiction; African Americans -- Fiction; Women slaves -- Fiction; Slavery -- Fiction; Tochter; Erwachsenwerden; Sklavin; Plantagenbesitzer; Familienleben; Sexueller Missbrauch; USA; United States -- History -- Civil War, 1861-1865 -- Fiction; USA -- Südstaaten; Jugendbuch; Historical fiction; War stories